ENGLISH TEACHERS' PERCEPTION OF ELT IN MERDEKA CURRICULUM AT SMKN DARUL ULUM MUNCAR ACADEMIC YEAR 2022/2023 - Ahmada, Adib; Maulida Wafiq Azizah (At- Ta'lim : Jurnal Pendidikan, 2023)
In 2020 Indonesia experienced the Covid-19 pandemic, resulting in a worsening learning crisis. The government issued an emergency curriculum policy. After running for one school year, the government found that using the emergency curriculum got better results than the previous curriculum. Moreover, in February 2022, the government began to apply the Merdeka curriculum. This research aims to find out and provide information about English teachers' perceptions of the Merdeka curriculum at SMKN Darul Ulum Muncar for the 2022/2023 academic year. The researcher focuses on teaching modules and the Strengthening Pancasila Student Profile Project (P5) in the Merdeka curriculum. For data collection, researchers use quantitative methods. Then for the research model with a survey model, researchers distributed questionnaires to nine English teachers at SMKN Darul Ulum Muncar. Moreover, this study found that English teachers' perception of the Merdeka curriculum at SMKN Darul Ulum Muncar was very good. The overall average score of teachers indicates this is 79, which is included in the interval range score of 72 < X, which means it is categorized as very good. In more detail, four teachers have good perceptions, and five other teachers have very good perceptions. This research provides valuable insights into how the Merdeka curriculum is received by English teachers at SMKN Darul Ulum Muncar, depicting a positive response to the curriculum change.